Case report: Whole exome sequencing and genome-wide methylation profiling of Czech dysplasia in a Chinese pedigree - Zhao, Mengfei; Zhang, Runrun; Chang, Cen; Jin, Yehua; Xu, Lingxia; Guo, Shicheng; Schrodi, Steven; He, Yong; He, Dongyi (Frontiers in Medicine, 2023)
Background: Czech dysplasia is a rare skeletal dysplasia with symptomology including platyspondyly, brachydactyly of the third and fourth toes, and early-onset progressive pseudorheumatoid arthritis. The disorder segregates in an autosomal dominant fashion. A specific missense mutation (R275C, c.823C>T) in exon 13 of the COL2A1 gene has been identified in German and Japanese families. Case Summary: We report the case of a Chinese female diagnosed with Czech dysplasia (proband) who carried a variant in the COL2A1 gene. Whole-exome sequencing (WES) identified the COL2A1 missense mutation (R275C, c.823C>T) in close relatives of the proband who exhibited the same disorder. Conclusion: This study is a thorough clinical and physiological description of Czech dysplasia in a Chinese patient.